Place: Interactive Learning Media Augmented Reality (AR) 3d In “Plant Cell” for 11th Grade Students - Nugraha, Adimas Nanda; Pramudita, Dias Aziz (Universitas Muhammadiyah Surakarta, 2022)
The era development, the rapid of technology, and the availability of mobile phone use for students in facilitating learning should be accompanied by familiarization of the use of media as one to support the learning. Biology is considered as a subject that requires more understanding and interpretation through its visualization. Moreover, the one focuses on “Plant Cell” material is rare. This research is further aimed at: (1) developing an interactive learning media Augmented Reality (AR) 3D in Biology material